Microfluidic devices powered by integrated elasto-magnetic pumps. Issue 22 (23rd October 2020) - Binsley, Jacob L.; Martin, Elizabeth L.; Myers, Thomas O.; Pagliara, Stefano; Ogrin, Feodor Y.
Abstract : Integrated elasto-magnetic pumps power portable microfluidic devices for point of care testing. Abstract : We show how an asymmetric elasto-magnetic system provides a novel integrated pumping solution for lab-on-a-chip and point of care devices. This monolithic pumping solution, inspired by Purcell's 3-link swimmer, is integrated within a simple microfluidic device, bypassing the requirement of external connections. We experimentally prove that this system can provide tuneable fluid flow with a flow rate of up to 600 μL h −1 . This fluid flow is achieved by actuating the pump using a weak, uniform, uniaxial, oscillating magnetic field, with field amplitudes in the range of 3–6 mT. Crucially, the fluid flow can be reversed by adjusting the driving frequency. We experimentally prove that this device can successfully operate on fluids with a range of viscosities, where pumping at higher viscosity correlates with a decreasing optimal driving frequency. The fluid flow produced by this device is understood here by examining the non-reciprocal motion of the elasto-magnetic component. This device has the capability to replace external pumping systems with a simple, integrated, lab-on-a-chip component.